If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2y = -15 Combine like terms: y + 2y = 3y 3y = -15 Solving 3y = -15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '3'. y = -5 Simplifying y = -5
| 8x=12x+38 | | 15x^4+x^3-52x^2+20x+16=0 | | 3(b-4)=12 | | 6y+5=26 | | x^2+5x+m+6=0 | | 5y-6=2y-15 | | 0.125(a+9)=4 | | 0.125(a+9)=2 | | x+y-17=x*y-42 | | 16+4x^2+4x^3+x^4=0 | | Y=4ln(6x-8) | | 4-x/x-1=5 | | (3x-4)=(x+4) | | A-7=27 | | 8y-3+y+7= | | (-10)+3x=8 | | 7x=22.75 | | 15.(x+2)=6.(2x+7) | | 9z+30=120 | | -5/3x=-4/3 | | (x+120)=x | | 26+30=90 | | x=x-120 | | 3x^2+x-154=0 | | 20logx=140 | | (x+4)*(x-2)-2=0 | | y-x^2=1 | | 3737x+77826x=7373828782 | | =cos(5x^2) | | 27.2m+15.7=85.94+0.8m | | 3737x+77826=7373828782 | | 9y+6y^2= |